Minimization of the perianal infection rate of hematological malignancies with agranulocytosis by quality control circle activity and patient–hospital–student win–win concept. Issue 6 (June 2018) - Jiang, Qianli; Zhang, Dan; Majaw, Jerry; Zhao, Chenjing; Chai, Yanyan; Xu, Zehua; Wang, Ruiting; Li, Xiaoli; Zou, Chun; Huang, Liting; Wu, Hansen; Hu, Pingling; et al.
Objective: The agranulocytosis-associated perianal infection (PI) rate ranges from 60% to 100% among patients with hematopoietic malignancies. In this study, we assessed the efficacy of a quality control circle (QCC) to minimize the PI rate. Methods: Among 274 patients with severe immunodeficiency (agranulocytosis of ≥2 weeks) in our bone marrow transplantation center, the PI rate was 17.20%. A QCC was established following the 10 steps of the plan-do-check-act (PDCA) model; this was scientifically supported by culturing the bacterial colony from patients' perianal skin to determine the sanitization effect and interval time. Because a warm aqueous solution of potassium permanganate is recommended for sanitization, the bacterial colony culture was also used to determine the proper drug concentration, water temperature, and soaking time. All procedures were standardized. Patients, hospital staff, and medical students were enrolled into the QCC team based on the patient–hospital–student (PHS) win–win concept. Results: After establishment of the PDCA model, the PI rate among 253 patients decreased from 17.20% to 5.93% and remained at 5.25% during the following year. The medical expenses and length of hospital stay consequently decreased. Conclusion: The QCC and PHS win–win concept can reduce the PI rate and promote medical quality.